2005
DOI: 10.1161/01.hyp.0000184653.75036.d5
|View full text |Cite
|
Sign up to set email alerts
|

Lipid Accumulation and Transforming Growth Factor-β Upregulation in the Kidneys of Rats Administered Angiotensin II

Abstract: Abstract-Abnormal lipid metabolism may play a role in progressive renal failure. We studied whether lipid accumulation occurs and whether lipid deposits are colocalized with transforming growth factor-␤1 (TGF-␤1) in the kidney of angiotensin II-infused animals. Oil red O staining showed marked lipid deposition in the tubular epithelial and vascular wall cells of angiotensin II-treated but not in norepinephrine-treated rats. Histological analyses showed that increased amounts of superoxide and intense TGF-␤1 mR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(38 citation statements)
references
References 38 publications
(51 reference statements)
5
32
1
Order By: Relevance
“…1, 2); these results stood in contrast with the exclusive co-localization of ferritin and heme oxygenase-1 (15). In addition, only a fraction of the mRNA expression of the genes tested was colocalized with lipid deposition, again in contrast to the exclusive co-localization of TGF-β1 mRNA and lipid deposition in the kidney (16,17).…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…1, 2); these results stood in contrast with the exclusive co-localization of ferritin and heme oxygenase-1 (15). In addition, only a fraction of the mRNA expression of the genes tested was colocalized with lipid deposition, again in contrast to the exclusive co-localization of TGF-β1 mRNA and lipid deposition in the kidney (16,17).…”
Section: Discussionmentioning
confidence: 92%
“…The sequence targeted for the amplification of DMT1 was a common region of DMT1 with or without iron-responsive element (IRE), which was designated here as IRE(+)DMT1 and IRE(−)DMT1, respectively. Rat cDNA corresponding to these iron metabolism-related genes were subcloned into a pGEM-T vector, and then in situ hybridization was performed as described previously (17). After digestion with a restriction enzyme and linearization of the plasmid, antisense and sense cRNA riboprobes were transcribed in vitro using the DIG RNA labeling Kit SP6/T7 (Roche Diagnostics, Basel, Switzerland).…”
Section: In Situ Hybridization Histological Analysesmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first instance, increased exposure to angiotensin II induces a rise in cell proliferation, particularly of mesangial cells (62) . As observed with other hormones, plasma concentrations of angiotensin II increase with obesity and, as noted for IGF-I and insulin, angiotensin II is also associated with lipid and collagen accumulation in renal tissue (63)(64)(65) . Long-term exposure to angiotensin II, due to its contractile actions as well as the subsequent increase in metabolic activity in proximal tubules, leads to an increase in oxygen consumption producing renal ischaemia (66) .…”
Section: Adult Obesity and Renal Healthmentioning
confidence: 56%
“…Activation of the renin-angiotensin system plays a key role in the progression of various diabetic complications and also leads to vascular dysfunction 7,8) . In a recent study, we showed that administration of angiotensin II caused marked lipid accumulation in the heart and kidney in a rat model of hypertension 9,10) . Furthermore, it has been reported that lipids are ligands for transcriptional regulators of the peroxisome proliferator-activated receptor (PPAR) family; therefore, regulating lipid delivery may have a significant impact on PPAR function 5) .…”
Section: Western Blot Analysismentioning
confidence: 99%